Tool path generation of contour parallel based on ant colony optimisation - Abdullah, Haslina; Ramli, Rizauddin; Abd Wahab, Dzuraidah; Abu Qudeiri, Jaber (UTM Press., 2016)
In today’s competitive market of manufacturing industry, shorter machining time is one of important factor for reducing the manufacturer’s cost. This paper presents the minimisation of machining time of computer numerical control (CNC) by eliminating the uncut region of sharp corner based on contour parallel milling method. Each uncut region at sharp corner is represented by uncut line which consists of two nodes in x and y directions. An Ant Colony Optimisation (ACO) method is used to optimize the tool path length because of its capability to find the shortest tool path length. The optimisation of tool path length based on ACO algorithm ascertained that the cutting tool remove the uncut line once and able to eliminate the uncut region in the shortest tool path length. To observe the effectiveness of the ACO performance, the simulation results are compared with the results obtained by the previous method. Finally the simulation results show the reduction of 5% machining time compared to previous method.